Existing social policies and their effects on the colombian population (2013)
This paper explores the impact of social policies adopted in Colombia from years ago, policies aimed at eradicating extreme poverty is analyzed to meet these goals the Government has created various programs that specialize in certain sectors of Families in extreme poverty, the goal is to highlight the work done and the advantages and disadvantages of adopting such policie